EMERGING ROLE OF ARTIFICIAL INTELLIGENCE AND BIG DATA IN DRIVING SUSTAINABLE GROWTH IN THE GLOBAL FOOD INDUSTRY - ., ADITYA (Food and Feed Research, 2025)
The integration of artificial intelligence (AI) and Big Data is emerging as a transformative force in the global food industry, driving sustainable growth through enhanced efficiency, productivity, reducing waste, improving resource management and decision-making capabilities. Recent advancements in AI and Big Data technologies, such as predictive analytics and machine learning, are revolutionizing agricultural practices by enabling precision farming, optimizing resource use and improving crop management systems. These technologies facilitate real-time monitoring of crop health, yield predictions and disease detection, thereby addressing critical challenges such as food insecurity and waste reduction. The application of AI and Big Data in the food supply chain enhances traceability and transparency, which are essential for ensuring food safety and quality. These technologies have further accelerated the adoption of digital solutions in the food sector, highlighting the need for resilient supply chains capable of adapting to disruptions. As the food industry grapples with the dual pressures of climate change and a growing global population, the role of AI and Big Data in promoting sustainable practices becomes increasingly vital. In addition to agricultural applications, AI and Big Data are reshaping business models within the food industry by fostering innovative marketing strategies and personalized nutrition solutions. The convergence of these technologies not only supports environmental sustainability but also enhances economic viability, paving the way for a more sustainable food ecosystem. Incorporating AI and Big Data into the global food industry fosters resilience against challenges such as climate change, resource scarcity and population growth. Therefore, by facilitating more sustainable and efficient operations, these technologies are revolutionizing food production, processing, distribution and consumption, thereby aligning the industry with the principles of environmental stewardship and global food security, in accordance with global sustainability objectives.